Influence of obesity in pulmonary function and exercise tolerance in obese women with obstructive sleep apnea - Vivian Maria Moraes Passos (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: To evaluate the influence of obesity on pulmonary function and exercise tolerance in women with obstructive sleep apnea (OSA). Subjects and methods: A descriptive analytic cross- sectional study was carried out. Thirty-nine (39) sedentary climacteric women, aged 45 to 60 years, were evaluated and submitted to polysomnography. The participants were divided into 4 groups: a) ‘eutrophic non-OSA’ (n = 13); b) ‘eutrophic OSA’ (n = 5); c) ‘obese non-OSA’ (n = 6); d) ‘obese OSA’ (n = 15). All subjects underwent clinical and anthropometric evaluation, followed by pulmonary function tests and 6-minute walk test (6MWT). Results: There was a significant difference in the predicted percentage values of FEV1/FVC when comparing ‘eutrophic OSA’ and ‘obese OSA’ (97.6% ± 6.1% vs. 105.7% ± 5.7%, respectively; p = 0.025). The other spirometric variables did not show any differences between the studied groups. There was no significant difference in the maximum distance walked when the ‘eutrophic non-OSA’, ‘eutrophic OSA’, ‘obese non-OSA’ and ‘obese OSA’ groups were compared. Conclusion: Considering the results of this study, OSA itself did not influence pulmonary function or functional capacity parameters compared to eutrophic women. However, not only isolated obesity but also obesity associated with OSA can negatively impact sleep quality and lung function.